Management of cervical lymph nodes for cN0 advanced glottic laryngeal carcinoma and its long-term results. (September 2014) - Ma, Hongzhi; Lian, Meng; Feng, Ling; Li, Pingdong; Hou, Lizhen; Liu, Hongchuan; Chen, Xiaohong; Huang, Zhigang; Fang, Jugao
Abstract Conclusions: Cervical lymph node metastatic rates tend to increase by T stage in cN0 glottic laryngeal carcinoma (GLC). Moreover, cervical lymph node metastasis (LNM) shows a sequential pattern according to the regions involved and LNM affects the prognosis. Objectives: To investigate factors that contribute to LNM of N0 (cN0) T2–T4 GLC and their effect on prognosis. Methods: A total of 212 GLC patients who had been admitted between December 2002 and January 2013 were retrospectively analyzed. They included 202 men and 10 women, median age 58.6 years (range 29–85 years), whose identified tumor stages included T2 (n = 81), T3 (n = 67), and T4 (n = 64). Relevant factors of cervical LNM were analyzed; multivariate analyses and receiver operating characteristic (ROC) curve were carried out to predict the metastasis and prognosis. Results: The overall metastatic rate of N0 GLC was 14.6%. T staging and pathological classification were the risk factors for LNM. Metastatic rates for levels II, III, and IV were 10.2%, 14.6%, and 2.5%, respectively. Approximate 4.2% of patients experienced LNM with no recurrence of laryngeal cancer. Overall 3- and 5-year survival rates were 85% and 80%, respectively, compared with 66% and 57%, respectively, among patients with LNM. The inter-group survival curve comparison was statistically significant (p = 0.012).